MAKNA TRADISI PEMOTONGAN JAWI DI DESA LIPAI BULAN KECAMATAN KERUMUTAN KABUPATEN PELALAWAN - Khairunnas "; Yasir " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The tradition of cutting jawi is one of the local wisdom of the Lipai Bulan community which has a certain meaning which symbolic meaning contained in the tradition of cutting jawi there are 2 namely physical and symbol, physical meaning in cutting jawi and tasteless while the symbol consists of cooking and festivity / thanksgiving. The purpose of this study is to find out the symbolic meaning and values contained in the tradition of cutting jawi.This study uses qualitative research methods with a symbolic interaction approach. The research subjects were community leaders and several people of Lipai Village who were involved in the tradition of cutting jawi. Data collection techniques carried out are through observation, interviews, and documentation.The results of this study indicate that the symbolic meaning of the tradition of cutting jawi in Lipai Bulan village consists of physical meanings which include tools and materials used in cutting jawi and seedling of fresh fruit with a specific meaning in each part and the social meaning of the tradition of cutting jawi in Lipai Bulan village consisting of cooking processions every activity is carried out in mutual cooperation is to be able to improve family attitudes, very solid cooperation, and quickly finished. In thanksgiving / festivity which also has certain meanings such as prayers offered by community leaders, this prayer is offered to the Almighty God, a form of expressing gratitude for the people because they are still given blessings and prosperity that never stop flowing. In the tradition of cutting jawi there are values which consist of social values, namely strengthening the relationship with fellow community members to maintain a sense of solidarity in diverse lives, cultural values can be seen how local wisdom is maintained and orchestrated and the community feels rewarded for still adhering to the culture and the tradition of inheritance and religious values show one form of gratitude, hope for blessing, and rejecting disaster (disaster) to the creator of the universe that has given grace and prosperity.Keyword : meaning, of cutting jawi